A Cumulative Spore Killing Approach: Synergistic Sporicidal Activity of Dilute Peracetic Acid and Ethanol at Low pH Against Clostridium difficile and Bacillus subtilis Spores. (22nd December 2015) - Nerandzic, Michelle M.; Sankar C, Thriveen; Setlow, Peter; Donskey, Curtis J.
Abstract : The synergistic combination of dilute peracetic acid and ethanol at low pH provides a novel approach for development of a rapid and effective method for reducing C. difficile spores on skin. Abstract: Background. Alcohol-based hand sanitizers are the primary method of hand hygiene in healthcare settings, but they lack activity against bacterial spores produced by pathogens such as Clostridium difficile and Bacillus anthracis . We previously demonstrated that acidification of ethanol induced rapid sporicidal activity, resulting in ethanol formulations with pH 1.5–2 that were as effective as soap and water washing in reducing levels of C difficile spores on hands. We hypothesized that the addition of dilute peracetic acid (PAA) to acidified ethanol would enhance sporicidal activity while allowing elevation of the pH to a level likely to be well tolerated on skin (ie, >3). Methods. We tested the efficacy of acidified ethanol solutions alone or in combination with PAA against C difficile and Bacillus subtilis spores in vitro and against nontoxigenic C difficile spores on hands of volunteers. Results. Acidification of ethanol induced rapid sporicidal activity against C difficile and to a lesser extent B subtilis . The addition of dilute PAA to acidified ethanol resulted in synergistic enhancement of sporicidal activity in a dose-dependent fashion in vitro. On hands, the addition of 1200–2000 ppm PAA enhanced the effectiveness of acidified ethanol formulations, resulting in formulations with pH >3 that were as effective as soap and water washing. Conclusions. Acidification and the addition of dilute PAA induced rapid sporicidal activity in ethanol. Our findings suggest that it may be feasible to develop effective sporicidal ethanol formulations that are safe and tolerable on skin.